Adaptation and validation of short scales for assessment of psychological distress in Iran: The Persian K10 and K6. Issue 3 (11th June 2018) - Hajebi, Ahmad; Motevalian, Abbas; Amin‐Esmaeili, Masoumeh; Rahimi‐Movaghar, Afarin; Sharifi, Vandad; Hoseini, Leila; Shadloo, Behrang; Mojtabai, Ramin
Abstract: Objectives: The aims of the study were to translate into Persian and culturally adapt the Kessler Psychological Distress Scales, K10 and K6, and to assess their reliability and validity. Method: The sample was recruited from primary health care (PHC) settings by quota nonprobability sampling, stratified by sex and age. Validity was assessed against the Composite International Diagnostic Interview (v2.1). The psychometric properties of K6 and K10 were also compared with the 12‐item General Health Questionnaire (GHQ‐12). Results: A total of 818 participants completed the questionnaire. Cronbach's alpha were 0.92 and 0.87 for K6 and K10, respectively. Optimal cutoff scores for detecting any mood or anxiety disorder in the past 30 days were 15 for K10 and 10 for K6. At these cutoff points, the measures had sensitivities of 0.77 and 0.73, specificities of 0.74 and 0.78, and positive predictive values of 0.48 and 0.52, respectively. Psychometric properties of K10 and K6 were similar to GHQ‐12. Conclusion: Persian K10 and K6 have acceptable psychometric properties as screening instruments for common mental health conditions. Given its brevity and similar psychometric properties to the longer instruments, the Persian K6 appears to be a suitable scale for use in PHC settings and, possibly, epidemiologic studies in Iran.